Implementasi Program Tribina dalam Meningkatkan Ketahanan Keluarga Perspektif Maslahah Mursalah - Rahmah Nurjannah, Nyayu; Zuraidah, Zuraidah (CV. Doki Course and Training, 2025)
The progress of modern times has led to increasing complexity in family issues, both from internal and external factors. Family resilience is a crucial instrument to counteract various negative impacts that may weaken family functions. This study aims to analyze the role of the Tribina program in strengthening family resilience in the Kampung Keluarga Berkualitas (KB) Mawar, Kelurahan 1 Ilir, Palembang. The research method employed is qualitative with a field research approach. Primary data were obtained through interviews, while secondary data were collected from literature, journals, and relevant documents. The data were analyzed descriptively and qualitatively using a deductive approach. The findings reveal that family resilience is measured through eight indicators as stipulated in Article 7 paragraph (2) of Government Regulation No. 87 of 2014, covering religious, socio-cultural, affection, protection, reproductive, socialization and education, economic, and environmental development functions. The Tribina program has been proven to significantly contribute to strengthening these eight family functions and is aligned with the concept of al-Mashalih al-Khams (religion, life, intellect, lineage, and wealth). Thus, the Tribina program serves as a key strategy to enhance family resilience while reinforcing sustainable family development.